Evaluation of Career Guidance Service Program Using the Kirkpatrick Model at SMK Negeri 3 Pariaman - Yudha Aditya Fiandra; Ambiyar Ambiyar; M Giatman; Wakhinuddin Wakhinuddin; Nurhasan Syah (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Career Guidance Service Program is a solution to help students to make career choices in order to become a professional in the future. However, it turns out that the current conditions and the reality on the ground are not as they should be. This study aims to evaluate how Reaction, Learning, Behavior and Result in the Career Guidance service program at SMK Negeri 3 Pariaman. This type of research uses evaluation research using the Kirkpatrick model which involves four components, namely the Reaction, Learning, Behavior and Result components. The method used in this research is a mixed method. Quantitative data were first collected using a questionnaire, then supplemented by qualitative data collected through interviews, observation and documentation. The overall results obtained from the evaluation research on the career guidance service program at SMK Negeri 3 Pariaman are good, overall all programs are running well, of course with a slight increase in the reaction and behavior components